Explaining naturalization and invasiveness: new insights from historical ornamental plant catalogs. Issue 20 (15th September 2016) - Lavoie, Claude; Joly, Simon; Bergeron, Alexandre; Guay, Geneviève; Groeneveld, Elisabeth
Abstract: We identified plant attributes associated with naturalization and invasiveness using century‐old ornamental plant catalogs from Québec (Canada). We tested the hypothesis that naturalization is determined by fewer factors than invasiveness, as the latter also requires dispersal, which introduces additional complexity. The approach we used took into account not only plant attributes as explanatory factors, but also propagule pressure, while accounting for phylogenetic relationships among species. Museum collections were used, in combination with scientific journal databases, to assess invasiveness. Particular attention was given to species that never escaped from gardens and thus represent cases of "failed" invasions. Naturalization in cold‐temperate environments is determined by fewer factors than invasion, but only if phylogenetic links between species are taken into account, highlighting the importance of phylogenetic tools for analyzing species pools not resulting from a random selection of taxa. Hardiness is the main factor explaining naturalization in Québec. Invasion requires dispersal, as shown by three significant variables associated with the spread of diaspores in the invasiveness model (seed weight, hydrochory, number of seed dispersal modes). Plants that are not cold‐hardy are likely to disappear from the market or nature, but the disappearance phenomenon is more complex, involving also seed dispersal abilities and propagule pressure. Factors contributing to naturalization or invasiveness may differ greatly between regions. Differences are due in part to the plant traits used in the models and the methodology. However, this study, conducted in a cold‐temperate region, sheds new light on what is likely a context (climatic)‐dependant phenomenon. Abstract : We identified plant attributes associated with naturalization and invasiveness using century‐old ornamental plant catalogs from Québec (Canada). Hardiness is the main factor explaining naturalization in Québec. Invasion requires dispersal. This study, conducted in a cold‐temperate region, sheds new light on what is likely a context (climatic)‐dependant phenomenon.